Tinjauan Historis – Teologis Terhadap Potrait Yesus Menurut Perjanjian Baru Dan Implikasinya Terhadap Teologi Perjanjian Baru - Kasieli Zebua; Melianus Hura (Sekolah Tinggi Teologi Syalom Bandar Lampung, 2022)
The Gospel is the Good News from God to mankind. The Gospel is God's eternal plan in His Only Begotten Son, Jesus Christ, revealed in His incarnation, ministry, suffering, death, resurrection until His coming. Jesus This is the basis and centrality in the Christian faith. Regarding Jesus Christ, many stories have been